Assessing the ovarian reserve in girls who survived childhood leukemia using anti-Mullerian hormone - Lalita Jingrukwong; Khomsak Srilanchakon; Supanun Lauhasurayotin; Kanhatai Chiengthong (Annals of Pediatric Endocrinology & Metabolism)
Purpose Acute leukemia is the most common form of malignancy in children; however, there is an absence of data regarding the long-term ovarian reserve of female survivors. The purpose of this investigation was to examine potential discrepancies in anti-Mullerian hormone (AMH) levels among female survivors of pediatric acute leukemia. Methods A cross-sectional study was conducted on female survivors aged 2 to 18 years who completed gonadotoxic chemotherapy sessions at least 1 year prior to evaluation. Based on Tanner staging, the participants were divided into pre-pubertal and pubertal groups. Serum AMH, follicle stimulating hormone (FSH), luteinizing hormone (LH), and estradiol were assessed. Results Three of 36 participants demonstrated low AMH levels in comparison to the adjusted age-reference range, whereas all participants had normal FSH and LH levels. However, the correlation between cumulative dose of cyclophosphamide and AMH level was not statistically significant. Conclusions Measurement of AMH level may not be beneficial in individuals who have received a cumulative dose of cyclophosphamide less than 5,400 mg/m2.